The Influence of Social Media on Improving Student Learning Achievement Through Extracurricular Activities - Darwan Darwan; Elpisah Elpisah; Saripuddin Saripuddin (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze the influence of social media on student learning achievement and extracurricular participation among fifth and sixth-grade students in Tondong Tallasa Sub-district, Pangkep Regency. A total of 64 students from three elementary schools were involved as research participants. A quantitative approach with a descriptive method was employed. Data were collected through interviews, observations, and questionnaires, then analyzed using the path analysis method to assess causal relationships between variables. The findings reveal that responsible use of social media significantly enhances student achievement and promotes active involvement in extracurricular activities. Future research could explore the impact of social media across broader demographic groups and investigate its long-term effects on student academic and personal development.